2021
DOI: 10.1111/acfi.12834
|View full text |Cite
|
Sign up to set email alerts
|

Migrant entrepreneurs and firm innovation

Abstract: This study examines the impact of entrepreneurs' migrant background on firm innovation as measured by spending on research and development and by the number of patents. We find that entrepreneurs' migrant background is positively related to firm innovation level, and that this relation is weakened by a less supportive environment. We also find that migrant entrepreneurs have a higher propensity to take risks than their local peers. Further analyses show that the relationship between migrant background and inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…We follow J. Gao et al. (2021) and match using a nearest‐neighbour propensity score with a 0.005 calliper. The matching includes 671 treated firms and 745 control firms, constituting an equal firm‐year observation of 1462 for both treated and control groups.…”
Section: Empirical Analysismentioning
confidence: 99%
“…We follow J. Gao et al. (2021) and match using a nearest‐neighbour propensity score with a 0.005 calliper. The matching includes 671 treated firms and 745 control firms, constituting an equal firm‐year observation of 1462 for both treated and control groups.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Recent research has addressed various factors that influence firm innovation. For example, Gao et al (2021) found that managers' immigrant background was positively correlated with corporate innovation. Miao et al (2020) proposed that wage inequality within companies encouraged managers to increase R&D investment and use bank loans to finance innovation, thus promoting it.…”
Section: Introductionmentioning
confidence: 99%